Implementation of English Language Learning Using Grammar Translation Method (GTM) To Improve Learning Outcomes of Grade 2 Students at SDS Al-Ittihadiah - Salsabila, Aruni; Amirul, Bani; Amsah, Dara Gustia; Nursyafitri, Dila; Purba, Rifaatur Rasyidah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
English subjects focus on developing communication, comprehension, pronunciation, and writing proficiency. Teachers should use effective methods such as Grammar Translation Method (GTM) for grammar rules and translation. Educators must understand different teaching approaches to teach English effectively, such as GTM for vocabulary learning. Therefore, this research focuses on an in-depth study of how the Application of English Learning Using Grammar Translation Method (Gtm) to Improve Learning Outcomes of Grade 2 Students at SDS Al- Ittihadiah. In this study using a qualitative approach with descriptive methods. Data collection techniques in qualitative research are observation, interviews, and documentation studies. In addition to using qualitative research, this research also uses literature research or library research. Based on the research and discussion, English teaching at SDS Al-Ittihadiah has developed to keep up with globalization. The GTM method is used in grade 2, where students must be able to read and write English first. GTM focuses on grammar and vocabulary, with teachers using grammar analysis and translation. The main priorities of this method are reading, writing and translation skills. In addition, GTM has increased students' interest in translating Indonesian to English and helped teachers in evaluating students' learning outcomes. Overall, GTM is effective in improving students' ability to learn English..